Comunidade de formação e prática pedagógica indígena: inclusão digital e identidade cultural - Pedrosa, Neide Borges (2011)
This research is linked to the research line of New Technologies in Education Graduate Program in Education at PUC-SP. We conducted an investigation in the context of the Indian villages of the ethnic and Macaw Hawk, who live in the Land of Lourdes affluent city of Ji-Paraná, Rondônia. Inspired by the ideals of a different school, the research referenced by the full appreciation of the cultures of indigenous peoples, affirmation and maintenance of its ethnic diversity. Hence the focus on digital inclusion in an emancipatory perspective, through which respects diversity as opposed to adaptation to a given model and imposed on indigenous communities. Was defined as general objective to investigate the establishment and implementation of digital environments in these villages as part of a process of digital inclusion of indigenous communities who live there, so as to provide concrete and objective conditions necessary to achieve the central axis of the study .This, in turn, aimed to know how was the arrival of ICT in school and the community. This required to interpret and understand the meanings visible and hidden attributes that the Indian ICT, as well as experiencing the feeling forward to the challenge of this include digital culture and at the same time, ensure the preservation of their culture. Among other reasons highlighted the question of the right of access to technological innovations and knowledge as a fundamental dimension of life in contemporary democratic societies. The methodology based on a qualitative approach, in which action and participation constituted fundamental aspects that allow a movement of actionreflection- action, concluding that indigenous peoples have a clarity that need access to information technologies and the globalized world strengthening ties among their peers and with other ethnic groups to thus strengthen the struggle for their interests and survival